FLEXIBLE SYNCHRONOUS REGULATION OF POWER ELECTRONIC BLOCKS OF TRANSFORMER-BASED PHOTOVOLTAIC STATIONS - OLESCHUK, Valentin (Journal of Engineering Science (Chişinău))
The paper presents the results of developing a scheme for synchronous pulse-width modulation (PWM) of signals in dual voltage source diode-clamped inverters (VSDCIs) used in grid-tied, transformer-based photovoltaic (PV) stations. This scheme is based on the continuous regulation of the switching frequency of the inverters relative to the magnitude of the DC voltages of the PV strings, ensuring equivalence of switching losses across each inverter. The proposed control and PWM techniques ensure the elimination of even-order harmonics and subharmonics in spectra of voltage at inverter-side windings of power transformer, helping to increase the operating efficiency of inverter-based PV stations. Simulation results showed a behavior of operation of dual-VSDCI-based PV installations with the proposed control strategy.